Handbook of IPv4 to IPv6 transition methodologies for institutional and corporate networks - Amoss, John 1941- (Auerbach Pub., 2008)
Addresses the migration and macro-level scalability requirements to support DoD/DIS/GAO drive for an IPv6-based US Government migration by 2007. This work discusses capabilities, network constructs, AutoConfiguration techniques, the suite of IPv6, and related protocols. It also examines Enterprise/Institutional network migration scenarios.